RESTORATION OF CONTROLLABILITY AND STABILITY OF THE AIRCRAFT IN THE CONDITIONS OF EMERGENCE IN THE SPECIAL SITUATION IN FLIGHT - Казак, В. М.; Шевчук, Д. О. (Science-based technologies, 2012)
The functional of efficiency, which system takes into reconfiguration of control surfaces, total charges, on control, diagnosing, prognostic, controlling, during the special situation on flight is offered. The functional of efficiency allows to estimate current efficiency in the conditions unfavorable external indignations and degrading internal processes.